Hetero‐Integration of Silicon Nanomembranes with 2D Materials for Bioresorbable, Wireless Neurochemical System (Adv. Mater. 14/2022). Issue 14 (7th April 2022) - Yang, Seung Min; Shim, Jae Hyung; Cho, Hyun‐U; Jang, Tae‐Min; Ko, Gwan‐Jin; Shim, Jeongeun; Kim, Tae Hee; Zhu, Jia; Park, Sangun; Kim, Yoon Seok; Joung, Su‐Yeon; Choe, Jong Chan; et al.
Abstract : Neurochemical Analyzers In article number 2108203, Chul‐Ho Lee, Dong Pyo Jang, Suk‐Won Hwang, and co‐workers demonstrate a soft, wireless, and bioresorbable neurochemical system that is designed to determine various concentrations of neurotransmitters as well as to monitor peripheral physiologies in a simultaneous manner. Such technology is motivated by the need for assessment and treatment of postoperative complications that may occur over a certain period of time after neurological surgeries.